Effects of Oat Varieties and Growing Locations on Seed-Borne Fungal Communities - Wang, Jianjun; Wei, Xuekai; Chen, Taixiang; White, James F.; Zhao, Guiqin; Li, Chunjie (Frontiers in Microbiology, 2021)
Many species of seed-borne fungi are closely allied with seed varieties and growing regions, including many seed-borne pathogens, but their species richness and distribution remain largely unknown. This study was conducted to explore the seed-borne fungal composition, abundance and diversity in Avena sativa (B7) and A. nuda (B2) seed samples collected from Baicheng (BB), Dingxi (DB) and Haibei (HB) city, using Illumina sequencing techniques. Our results show that a total of 543707 sequences were obtained and these were assigned to 244 operational taxonomic units (OTUs) with 97% similarity. Oat varieties and growing locations had a significant difference on seed-borne fungal diversity. HB had a higher fungal diversity than BB and DB, Shannon diversity and ACE richness index of fungal in HB seeds was significantly higher than in BB and DB (P＜0.05). In different varieties, both taxon richness and evenness of B7 seeds was significantly higher than B2 (P＜0.05). A total of 4 fungal phyla and 26 fungal genera were detected. Ascomycota was the dominant phylum and Alternaria sp. was the most abundant genus in B2 and B7 oat seeds from different regions. Mycosphaerella sp. had a higher abundance in HB7 and DB7, respectively, Epicoccum sp. had a higher abundance in HB7 and BB7. The results of alpha and beta diversity analysis revealed the presence of different effects in fungal communities of different varieties and regions of oat, especially in seed pathogenic fungi distribution. Structural equation modeling also explained oat varieties and growing regions have significant influences on seed-borne fungal abundance, composition and diversity. This study demonstrated that the differences of varieties and regions are the main factors resulting in the changes of seed-borne fungal community of oat.